Review on Diffuser Augmented Wind Turbine (DAWT) - Alquraishi, Balasem Abdulameer; Asmuin, Nor Zelawati; Mohd, Sofian; Abd Al-Wahid, Wisam A.; Mohammed, Akmal Nizam (International Journal of Integrated Engineering, 2019)
Wind energy technology is one of the fastest growing alternative energy technologies. However, conventional turbines commercially available in some countries are designed to operate at relatively high speeds to be appropriately efficient, limiting the use of wind turbines in areas with low wind speeds, such as urban areas. Therefore, a technique to enhance the possibility of wind energy use within the range of low speeds is needed. The techniques of augmenting wind by the concept of Diffuser Augmented Wind Turbine (DAWT) have been used to improve the efficiency of the wind turbines by increasing the wind speed upstream of the turbine. In this paper, a comprehensive review of previous studies on improving or augmentation power of Horizontal Axis Wind Turbines (HAWT) have been reviewed in two categories, first related with relative improvement of energy by improving the aerodynamic forces that affecting on HAWT in some different modifications for blades. Second, reviews different techniques to the augment the largest possible amount of power from HAWT focusing on DAWTs to gather information,helping researchers understand the research efforts undertaken so far and identify knowledge gaps in this area. DAWTs are studied in terms of diffuser shape design, sizing of investigation and geometry features which involved diffuser length, diffuser angle, and flange height. The conclusions in this work show that the use of DAWT achieves a quantum leap in increasing the production of wind power, especially in small turbines in urban areas if it properly designed. On the other hand, shrouding the wind turbine by the diffuser reduces the noise and protects the rotor blades from possible damage.